Assessment of zinc sources and levels for urea coating to achieve higher productivity and soil fertility in spring maize (Zea mays) - SEPAT, SEEMA; SINGH, HARMINDER; SINGH, A K (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2021 and 2022 at the research farm of ICAR-Indian Institute of Maize Research, Ludhiana, Punjab to study the efficacy of zinc oxide and zinc sulphate for urea coating to achieve higher productivity in maize (Zea mays L.). Experiment was laid out in a randomized block design (RBD) comprised of 11 treatments, viz. no Zn; 0.05% of Zn through ZnO; 0.12% of Zn through ZnO; 0.24% of Zn through ZnO; 0.47% of Zn through ZnO; 0.95% of Zn through ZnO; 0.26% of Zn through ZnSO4; 0.52% of Zn through ZnSO4; 1.03% of Zn through ZnSO4; 2.07% of Zn through ZnSO4; and 4.15% of Zn through ZnSO4, replicated thrice. Results indicated that grains/cob and cob weight/plant recorded higher with 1.03%, 2.07% and 4.15% of Zn through ZnSO4 compared to no Zn. Zn at 2.07% (5.68 and 6.36) and 4.15% (5.71 and 6.37) through ZnSO4 recorded higher grain yield followed by 0.95% of Zn (5.50 and 6.23) through ZnO and 1.03% (5.42 and 6.25) of Zn through ZnSO4 in 2021 and 2022. A higher Zn content in grain was registered with 4.15% (27.70 and 27.87 mg/kg) and 2.07% (26.33 and 27.67 mg/kg) of Zn through ZnSO4. Overall, Zn at 2.07% through ZnSO4 was found suitable for urea coating to enhance productivity, soil enzymatic activities and residual soil fertility in spring maize.